Comparison of Shear Bond Strength Between HEMA-Based and Non-HEMA Bonding Agents on Dentin Surface - Asmah, Nur; Mattulada, Indrya Kirana; Arsyad, M Aksa (Dentistry Faculty, 2024)
Background: Resin composite restorative materials have become increasingly popular in dental practice in recent decades due to their esthetic properties that meet patient demands. Adhesive ability predicts the durability of a restoration to a certain extent. It is hoped that the filling material will not come off easily and will function optimally in the oral cavity during attachment to the tooth structure. Bonding material is needed to attach the composite to dentin. The choice of HEMA and non-HEMA-based bonding materials on the dentin surface influences the bond strength test results, including the shear strength test. Objective: to analyze the shear attachment strength of HEMA and non-HEMA-based bonding after application to the dentin surface. Materials and Methods: This research is an experimental laboratory with a post-test without a control group design. The samples were bovine incisor teeth (N=32), namely HEMA-based Palfique Bond bonding (n=16) and non-HEMA-based G-Bond bonding (n=16) with Palfique LX5 composite restorations for HEMA and G- nial composite for non-HEMA with a diameter of 5 mm and a thickness of 3 mm. The shear bond strength was tested using a Universal Testing Machine (Shimadzu, Japan). Results: Based on the results of research using the T-test, it show a significant difference in shear bond strength between HEMA and non-HEMA-based bonding, with a significance of ( 0.05). Conclusion: Non-HEMA-based bonding materials have higher shear strength than HEMA-based bonding after application to the dentin surface.